Improved Retting Technology of Jute for quality fibre production - Majumdar, B.; Satpathy, S. (Indian Farming, 2015)
The CRIJAF has developed a talcbased microbial formulation consisting of three different strains of pectinolytic bacteria Bacillus pumilus very useful for quality jute/mesta fibre production in the stagnant water. By using this talc based formulation in natural retting tank, the retting duration was reduced by 6 to 7 days with improvement in fibre quality by 2 to 3 grades. Jute and mesta farmers of Andhra Pradesh and West Bengal have got higher price for the fibre produced by using this formulation. Farmers could earn an additional income of ` 6000 to 9000/ ha by spending only Rupees 675 to 900 from one hectare of jute/mesta crop over traditional method of retting by following this microbial talc mediated based formulation.